A case of tetrophthalmia with unilateral synophthalmia in an unborn fetus of blue shark Prionace glauca (Carcharhiniformes, Carcharhinidae) - Pastén-Marambio, Víctor; Hevia-Hormazábal, Valentina; Acuña, Enzo; Vega, Alonso (Revista de Biología Marina y Oceanografía, 2018)
This study describes and classifies a case of multiple malformations in an unborn blue shark Prionace glauca fetus, which was extracted from a gravid female captured during a research campaign addressed to the biological study of sharks in northern and central Chile. The analyzed specimen shows tetrophthalmia with unilateral synophthalmia, anomaly characterized by the existence of 4 ocular globes, two of which are partially fused. In addition, the axial skeleton of the fetus shows thoracic lordosis and helical torsion in the abdominal-caudal portion. This is the first world report of tetrophthalmia with unilateral synophthalmia in chondrichthyans.